Untargeted metabolomics as a tool to assess the impact of dietary approaches on pig gut health: a review - Chen, Li-Hsuan; Canibe, Nuria; Curtasu, Mihai Victor; Hedemann, Mette Skou (Journal of animal science and biotechnology, 2025)
Metabolomics utilizes advanced analytical profiling techniques to comprehensively measure small molecules in cells, tissues, and biological fluids. Nutritional metabolomics studies in pigs have reported changes in hundreds of metabolites across various sample types, including plasma, serum, urine, digesta, and feces, following dietary interventions. These findings can help identify biomarkers of gastrointestinal functionality and beyond, as well as investigate mechanistic interactions between diet, host, microbiome, and metabolites. This review aims to summarize the current literature on nutritional metabolomics in pigs and its use to investigate how different dietary approaches impact the gut health of pigs. Here, we critically assessed and categorized the impact of the main macronutrients—carbohydrates, proteins, and fats—along with feed additives such as amino acids, bile acids, and probiotics, as well as feeding strategies like creep feeding, milk replacer introduction, and time-restricted feeding, on the pig metabolome. Additionally, we discuss the potential modes of action of the key affected metabolites on pig gut health.